Energy-Efficient Synthesis and Superior Thermoelectric Performance of Sb-doped Mg2Si0.3Sn0.7 Solid Solutions by Rapid Thermal Explosion. (August 2020) - Zhang, Qiang; Fan, Jianfeng; Fan, Wenhao; Zhang, Hua; Chen, Shaoping; Wu, Yucheng; Tang, Xinfeng; Xu, Bingshe
Graphical Abstract: Sb-doped Mg2 Si0.3 Sn0.7 solid solutions have been prepared by ultrafast and low-cost thermal explosion (TE) combined with plasma activated sintering (PAS) for the first time, exhibiting superior thermoelectric figure of merit ZT including peak ZT peak and average ZT ave . Highlights: Mg2 (Si0.3 Sn0.7 )1-x Sbx solid solutions were synthesized by fast thermal explosion method within 1 min. Sb doping improves the power factor and the thermoelectric figure of merit. Structural homogenization is beneficial to high thermoelectric performance of Sb-doped Mg2 Si0.3 Sn0.7 materials. Abstract: Both low cost and high performance play pivotal roles in the commercial application of thermoelectric materials. Herein, a fast, facile and inexpensive thermal explosion (TE) was utilized to prepare eco-friendly Mg2 (Si0.3 Sn0.7 )1-x Sbx solid solutions. The phase transformation during the TE process was investigated. The criterion for differentiating TE from conventional solid-state reaction (SSR) was also illustrated, i.e. whether self-propagating high-temperature synthesis (SHS) happens. With Sb doping, carrier density rises and bipolar conduction in high-temperature range is effectively inhibited. Consequently, the dimensionless thermoelectric figure of merit ZT peak and ZT ave are enhanced, which are decent compared with the reported data. Although a comparative analysis of thermoelectric properties suggests that structural homogenization obtained by SSR instead of TE is conducive to high ZT for Mg2 Si0.3 Sn0.7 materials, the low-cost TE approach can be easily implemented with attributes of high energy efficiency, fast synthesis and large-scale production, thereby quite worth promoting for other thermoelectric materials.